ISOPHOT: capabilities and performance. - Lemke, Dietrich; Klaas, U.; Abolins, J.; Abraham, P.; Acosta-Pulido, J.; Bogun, S.; Castañeda Cortés, Héctor Mauricio; Groezinger, U.; Grün, Eberhard; Haas, Martin; Hajduk, C.; Hall, G.; et al. (Astronomy and astrophysics, 1996)
ISOPHOT covers the largest wavelength range on ISO from 2.5 to 240μm. Its scientific capabilities include multi-filter and multi-aperture photometry, polarimetry, imaging and spectrophotometry. All modes can optionally include a focal plane chopper. The backbone of the - photometric calibration are internal standard sources checked against celestial primary standards. The instrument is in excellent condition with all components functioning properly. There is increased detector noise due to the ionizing cosmic radiation affecting the detectability of the faintest sources. All lessons learnt from operating the - instrument in space are continously being implemented in the standard data reduction software packages available to every observer. Particular strengths of the instrument include the detectability of very cold sources, high resolution mapping and fast spectrophotometry.The far infrared serendipity sky survey performed during slews of the satellite has successfully started.